PENGARUH KOMITMEN ORGANISASI DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA DALAM UPAYA MENINGKATKAN KINERJA PEGAWAI - Mini - Setiyarti; Mulyanto - - (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2013)
ABSTRACT The research result shows that 1) the influence significant of a organization commitment toward the employees job satisfaction, 2) the influence insignificant of a job discipline toward the employees job satisfaction, 3) the influence insignificant of a organization commitment toward the employees performance, 4) the influence significant of a job discipline toward the employees performance, 5) the influence significant of a job satisfaction toward the employees performance, 6) path analysis show that: a) the influence of organization commitment has direct influence toward the employees performance dominant compare the influence a organization commitment toward the employees performance via a job satisfaction, b) the influence of job discipline has direct influence toward the employees performance dominant compare the influence a job discipline toward the employees performance via a job satisfaction, 7) the employees performance explains organization commitment and job discipline with job satisfaction as intervening variable and while its explained by other factors which are involved in the regression model such as a motivation, leadership, job environment, communication and organization culture variable, 8) the influence organization commitment and job discipline toward the employees performance via job satisfaction. Keywords: organization commitment, job discipline, performance job satisfaction,